Woolenization of Jute Fibre - Mia, Rony; Islam, Md. Ariful; Ahmed, Bulbul; Mojumdar, Jalal Ibn Amin (European Scientific Journal, ESJ, 2017)
Once upon a time, Jute was called the golden fibre of Bangladesh. Due to some problems and growth of modern technology, the market share of jute has decreased. In this paper, the effect of Woolenization of jute fibre was described. It also shows how the physical and chemical properties of jute have been changed by alkali-treatment as well as its structure. It was demonstrated that this kind of treatment leads to several changes in its structure which has turned to a near wool structure. These works are done by different concentrations of different alkalis. Finally, 15% NaOH treatment of jute show maximum woolenized properties where we obtain softened and swollen jute. Conclusively, we have made some other products from woolenized jute fibres such that if introduced into our world market, it can increase the market share of jute fibre.